1994
DOI: 10.1002/path.1711730305
|View full text |Cite
|
Sign up to set email alerts
|

DNA in situ hybridization as a diagnostic tool in the discrimination of melanoma and spitz naevus

Abstract: As the clinical and histological differential diagnosis between Spitz naevus and cutaneous melanoma may be very difficult, we have investigated whether DNA in situ hybridization maybe helpful in resolving this problem. To this end, routinely-processed paraffin sections of 15 typical Spitz naevi, 15 typical nodular melanomas, and five cases originally misdiagnosed as Spitz naevi but which later metastasized and were reclassified as melanoma were analysed using a method previously described (De Wit et al., J Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…27 Finally, nodular melanoma has been claimed to exhibit more prominent aneuploidy. 28 Here, we show that both clinicopathological subtypes of melanoma also differ in the expression of securin. Analysis of our previous oligonucleotide microarray data revealed that hPTTG1 overexpression in the vertical growth phase of malignant melanoma was significantly associated with shortened 4-year DMFS.…”
Section: Discussionmentioning
confidence: 69%
“…27 Finally, nodular melanoma has been claimed to exhibit more prominent aneuploidy. 28 Here, we show that both clinicopathological subtypes of melanoma also differ in the expression of securin. Analysis of our previous oligonucleotide microarray data revealed that hPTTG1 overexpression in the vertical growth phase of malignant melanoma was significantly associated with shortened 4-year DMFS.…”
Section: Discussionmentioning
confidence: 69%
“…12 De Wit et al performed DNA in situ hybridization using a chromosome-1 centromere probe on 15 Spitz nevi, 15 typical melanomas, and 5 problematic Spitz tumors that were classified initially as Spitz nevus and that later metastasized or displayed a malignant phenotype on recurrence. 40 In three of five problematic Spitz tumors and in many of the typical melanomas, those authors demonstrated supernumerary aberrations of chromosome 1 suggestive of aneuploidy, whereas Spitz nevi were euploid. 40 When these findings are coupled with reports of atypical, controversial, or problematic Spitz tumors disseminating with a lethal outcome, 2,7,14,15,26,[47][48][49] it is completely reasonable and tenable to regard an atypical Spitz tumor found in the lymph node parenchyma as biologically malignant.…”
Section: Discussionmentioning
confidence: 96%
“…DNA in situ hybridization using a chromosome-1 centromere probe on routinely processed paraffin sections reportedly showed a clear difference in the number of aberrant (aneuploid) nuclei between Spitz nevi and melanoma. 40 When it was applied to five problematic Spitz tumors that initially were misdiagnosed as Spitz nevi and that metastasized later, the technique retrospectively identified three of five tumors as melanoma. 40 Recently, Bastian et al, employing the technique of comparative genomic hybridization, observed no chromosomal aberrations in 13 of 17 Spitz nevi and found gains in the p arm of chromosome 11 or chromosome 7q21-qter in the remaining 4 Spitz nevi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathological criteria were evaluated, accompanied by immunohistochemical, ultrastructural, and molecular studies. [1][2][3][4][21][22][23][24] The only study, to our knowledge, that searched for LOH in Spitz nevi was by Healy et al, 5 who reported interstitial deletions at chromosome 9p in fewer than 10% of Spitz nevi.…”
Section: -17mentioning
confidence: 99%